PENGARUH MODEL MAKE A MATCH BERBANTU MEDIA FLASH CARD MAPU TERHADAP HOTS IPAS SISWA KELAS V SD - Silvi Yunita Wulandari; Yulina Ismiyanti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
The Higher Order Thinking Skills (HOTS) of elementary school students still need to be improved because the learning tends to be teacher-centered and does not actively involve the students. This study aims to determine the effect of the Make a Match learning model assisted by MAPU Flash Card media on HOTS abilities in fifth-grade elementary school IPAS learning. The research uses a quantitative approach with a One Group Pretest-Posttest design involving 24 fifth-grade students. Data were obtained thru descriptive tests before and after the treatment, and then analyzed using validity, reliability, normality tests, and the Paired Sample T-Test. The research results show an increase in the average score from 71.57 in the pretest to 85.42 in the posttest with a significance value < 0.05. Based on these results, it can be concluded that the Make a Match learning model assisted by MAPU Flash Card media has a positive effect on improving the HOTS IPAS abilities of fifth-grade elementary school students.